Cranberry Juice Consumption Lowers Markers of Cardiometabolic Risk, Including Blood Pressure and Circulating C-Reactive Protein, Triglyceride, and Glucose Concentrations in Adults. Issue 6 (22nd April 2015) - Novotny, Janet A; Baer, David J; Khoo, Christina; Gebauer, Sarah K; Charron, Craig S
Abstract: Background: Cardiometabolic risk is the risk of cardiovascular disease (CVD), diabetes, or stroke, which are leading causes of mortality and morbidity worldwide. Objective: The objective of this study was to determine the potential of low-calorie cranberry juice (LCCJ) to lower cardiometabolic risk. Methods: A double-blind, placebo-controlled, parallel-arm study was conducted with controlled diets. Thirty women and 26 men (mean baseline characteristics: 50 y; weight, 79 kg; body mass index, 28 kg/m 2 ) completed an 8-wk intervention with LCCJ or a flavor/color/energy–matched placebo beverage. Twice daily volunteers consumed 240 mL of LCCJ or the placebo beverage, containing 173 or 62 mg of phenolic compounds and 6.5 or 7.5 g of total sugar per 240-mL serving, respectively. Results: Fasting serum triglycerides (TGs) were lower after consuming LCCJ and demonstrated a treatment × baseline interaction such that the participants with higher baseline TG concentrations were more likely to experience a larger treatment effect (1.15 ± 0.04 mmol/L vs. 1.25 ± 0.04 mmol/L, respectively; P = 0.027). Serum C-reactive protein (CRP) was lower for individuals consuming LCCJ than for individuals consuming the placebo beverage [ln transformed values of 0.522 ± 0.115 ln(mg/L) vs. 0.997 ± 0.120 ln(mg/L), P = 0.0054, respectively, and equivalent to 1.69 mg/L vs. 2.71 mg/L back-transformed]. LCCJ lowered diastolic blood pressure (BP) compared with the placebo beverage (69.2 ± 0.8 mm Hg for LCCJ vs. 71.6 ± 0.8 mm Hg for placebo; P = 0.048). Fasting plasma glucose was lower ( P = 0.03) in the LCCJ group (5.32 ± 0.03 mmol/L) than in the placebo group (5.42 ± 0.03 mmol/L), and LCCJ had a beneficial effect on homeostasis model assessment of insulin resistance for participants with high baseline values ( P = 0.035). Conclusion: LCCJ can improve several risk factors of CVD in adults, including circulating TGs, CRP, and glucose, insulin resistance, and diastolic BP. This trial was registered at clinicaltrials.gov as NCT01295684.